Study on Corrosion Regularity and Mechanism of a Gathering and Transportation Pipeline in Jiyuan Oilfield - Lu, Wei; Hong, Guangfu; Zheng, Yuqian; Feng, Yan; Wang, Jian; Liu, Ruixuan; Huang, Changhe (International Journal of Electric Power and Energy Studies, 2024)
Aiming at the serious problem of corrosion of surface pipelines in Jiyuan Oilfield, this paper analyzes the corrosion law and corrosion mechanism of a gathering pipeline in Jiyuan Oilfield based on a variety of experiments. Research shows: through the spectrometer on the sampling pipe L245N composition analysis shows that the main elements of the pipeline tubing to meet the national standard requirements; the analysis of corrosion products and bacterial species shows that the corrosion type of this gathering pipeline is mainly CO2 corrosion and bacterial corrosion; based on the corrosion hanging experiment, it can be seen that the temperature in the temperature range of 10℃ 50℃, with the increase in temperature corrosion rate becomes larger, the pressure on the pipeline corrosion rate has less impact; based on the results of water quality analysis and pipe corrosion microscopic morphology observation, the pipeline extracted water Cl- ion content is high, there is pitting corrosion, especially weld corrosion is more serious.